PWE-215 An isolated abnormal chromogranin B is associated with pancreato-duodenal nets and the presence of liver metastases. (22nd June 2015) - Basuroy, R; Sherwood, R; Srirajaskanthan, R; Ramage, J
Abstract : Introduction: Chromogranin B (CgB) is a soluble secretory protein like chromogranin A (CgA) that has been reported to be elevated in patients with neuroendocrine tumours (NETs) but is not routinely assessed. This study explores whether an abnormal CgB paired with a normal CgA provides any useful clinical information in NET patients. Method: A prospective NET database (01/2007–11/2014) was interrogated for paired radioimmunoassay CgA (two assays; normal <6 nmol/L and 60 pmol/L) and CgB (two assays, normal <3 nmol/L, <150 pmol/L) results. Results: 1161 paired CgA and CgB results (479 patients) were retrieved. 51 patients had an isolated abnormal paired CgB (79 results; mean CgB result=2.68xULN); 2 patients were excluded as coding error. Primary sites were 24 pancreas, 9 small bowel, 4 rectal, 3 duodenal, 3 unknown, 2 duodenal-jejunal, 2 pre-sacral, 1 caecal and 1 lung. In 8/9 small bowel NETs, the CgB was raised in isolation on only one occasion on longitudinal testing. The tumour grades were 24 G1, 18 G2, 4 G3 and 3 unknown. Liver metastases were present in 38/49 patients. Conclusion: An isolated abnormal paired CgB was observed in 11% of NET patients. In 59% of patients it was associated with a pancreatic or duodenal primary NET. In 78% liver metastases were present. Further assessment is required to establish the role of CgB when paired with CgA as a biomarker of clinical utility in the diagnosis, prognosis and therapeutic monitoring of NETs. Disclosure of interest: None Declared.